Experience report: The applicability of Orem's theory during nursing consultation (Research, Society and Development, 2023)
This is a descriptive study, of the experience report type, developed based on academic experience during the supervised internship in the year 2023. The objective is to report an experience related to the development of the nursing process based on the Self-Care Deficit Nursing Theory (TDAE, in Portuguese). The study was conducted with a 67-year-old patient who came to the outpatient clinic for a nursing consultation. Orem's theory emphasizes the individual's role in caring for their own health, a crucial aspect to empower patients to take responsibility for their self-care needs, thereby increasing independence and consequently improving their quality of life. When the theory is integrated into the Nursing Process (SAE, in Portuguese), it helps promote a more holistic and patient-centered approach to nursing practice. In this way, we can achieve better health outcomes and increased patient satisfaction.